2003
DOI: 10.1063/1.1536265
|View full text |Cite
|
Sign up to set email alerts
|

Ge island formation on stripe-patterned Si(001) substrates

Abstract: Self-assembled Ge islands were grown by solid-source molecular-beam epitaxy on the submicron stripe-patterned Si(001) substrates at 650 °C. Atomic-force microscopy shows that the Ge islands grow preferentially at the sidewall of the Si stripes, oriented along the [−110] direction. The migration of the Ge adatoms from the top terrace down to the sidewall accounts for the island formation at the sidewall of the stripes. However, most of the Ge islands are formed on the top terraces when the patterned stripes are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 21 publications
1
42
0
Order By: Relevance
“…For this purpose new approaches were developed based on a combination of lithography and selforganized growth. 6 Long range ordering in two dimensions using either selective epitaxial growth through oxide masks 7 or direct growth on prepatterned substrates [8][9][10] was successfully demonstrated and excellent size homogeneities were reported. 11 However, the island formation and subsequent evolution on pit-patterned Si͑001͒ substrates are still not completely understood.…”
Section: G Bauermentioning
confidence: 99%
“…For this purpose new approaches were developed based on a combination of lithography and selforganized growth. 6 Long range ordering in two dimensions using either selective epitaxial growth through oxide masks 7 or direct growth on prepatterned substrates [8][9][10] was successfully demonstrated and excellent size homogeneities were reported. 11 However, the island formation and subsequent evolution on pit-patterned Si͑001͒ substrates are still not completely understood.…”
Section: G Bauermentioning
confidence: 99%
“…8 Ge SAQD are preferentially grown at the edges of selectively grown Si mesas in etched SiO 2 windows, 9,10 while they preferentially grow at the sidewalls of pure Si stripes. 11 These phenomena were discussed from the point of view of either energetics or kinetics. However, no detailed discussion about the growth of SAQD on patterned substrates has been presented so far.…”
Section: Introductionmentioning
confidence: 99%
“…1 Recently, it was shown that the combination of lithographic etching techniques and the SK growth mode provides a potential to grow long-range spatially ordered SAQD. [7][8][9][10][11][12][13] Some interesting phenomena have been observed during the growth of SAQD on patterned substrates. For instance InAs SAQD can be preferentially grown either on the top terraces or at the sidewalls or at the trenches of stripe-patterned GaAs substrates.…”
Section: Introductionmentioning
confidence: 99%
“…InAs QDs grown on this surface is smaller and some of the QDs are situated on the terraced surface isolated from the atomic steps. This will be related to the grown strained layer which changes into the preferential growth of islands on the terrace surface [6]. The surface migration on the initial GaAs surface without terraced structures as well as the suggested modification of the surface migration processes of adatoms will be related to the larger QD size distribution and may result in the different optical quality of the grown InAs QDs.…”
Section: Resultsmentioning
confidence: 99%
“…The above observation of the QD sizes and densities will be summarized as follows: The increase of the QD sizes on the atomically terraced GaAs surfaces prepared with the in-situ etching process shown in Fig. 3(a) will be attributed to the enhanced surface migration on the terraced surface [6]. The enhanced surface migration on the terrace surface will result in the edge growth of the QDs [7] and also increase the probability of coalescence of QDs, which eventually will result in the increase of the average QD size.…”
Section: Methodsmentioning
confidence: 99%